Inovasi Pembelajaran PAI di Majelis Taklim Perempuan Miftahul Jannah Kecamatan Teluk Naga, Tangerang, Banten - Irfan, Ahmad; Soejono, Sri Rosmalina; Setiady, Dicky (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2023)
Majelis taklim as one of the non-formal educational institutions in Indonesia seems to have to grapple with the progress and development of the times. Moving further without keeping up with the pace of the times will cause the majelis taklim to continue lagging behind. This research aims to uncover the forms of innovation in the majelis taklim, as well as the inhibiting and supporting factors that can influence its development. The research utilizes qualitative research methods through descriptive-analytical data analysis.The results of this research reveal that the innovation in the majelis taklim Miftahul Jannah primarily lies in the established curriculum and existing management structure. The supporting factor for innovation in the majelis taklim is the cohesion among the congregants, administrators, and mentors. On the other hand, the inhibiting factor revolves around the inability of the majelis taklim to achieve economic self-sufficiency.